1990
DOI: 10.1209/0295-5075/11/1/008
|View full text |Cite
|
Sign up to set email alerts
|

Universal Form of the Low-Energy (2 to 10 meV) Vibrational Spectrum of Glasses

Abstract: By means of inelastic cold neutron scattering the density of vibrational states (DVS) has been determined for a series of vitreous materials: SOz, As2& and metallic glass MgToZnso.In the low-energy range of the spectrum (E -(2 i 10) meV) for these materials DVS reveals a universal, but non-Debye form. The data obtained are compared to different models. A comparison with the Raman scattering data provides the spectral dependence for the coupling of the light to the vibrational excitations.The most important dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(93 citation statements)
references
References 15 publications
5
86
0
2
Order By: Relevance
“…If it is assumed that excitations in disordered systems have no well-defined wave vector q, then they can contribute to the light scattering spectra. 201 The first order Raman intensity I() is written in the form…”
Section: D14 Do Boson Peaks Measure Cluster Dynamics or Cage Rattlmentioning
confidence: 99%
See 1 more Smart Citation
“…If it is assumed that excitations in disordered systems have no well-defined wave vector q, then they can contribute to the light scattering spectra. 201 The first order Raman intensity I() is written in the form…”
Section: D14 Do Boson Peaks Measure Cluster Dynamics or Cage Rattlmentioning
confidence: 99%
“…197 However, a comparison with inelastic neutron scattering data indicated that the boson peak is related to an excess in the vibrational density of states. 201 Several models have been proposed to explain the boson peak. One model 193 assumed that the glass is composed of nanometric scale inhomogeneities, and g() is the density of vibrational excitations localized in the inhomogeneities.…”
Section: D14 Do Boson Peaks Measure Cluster Dynamics or Cage Rattlmentioning
confidence: 99%
“…На температурній кривій теплопровідності k(T) стекол нижче 1К типовою є залежність близька до T 2 , вище 1К в околі 10 К виявлено температурно-незалежне плато і далі , вище плато, спостерігається монотонний ріст теплопровідності [1][2][3][4][5][6][7][8][9][10]. Дослідження k(T) для склоподібного As2S3 були спочатку проведені в околі плато [2] , а в температурному інтервалі понад плато представлені в [3,5].…”
Section: низькотемпературна теплопровідність і бозонний пік в склоподunclassified
“…The glass is known to exhibit a variety of photoinduced effects [1][2][3][4][5][6][7]. The most famous may be the defect formation and radiation compaction in silica glasses which is now commercially utilized for producing Bragggrating fibres.…”
Section: Photoinduced Changes In Glassesmentioning
confidence: 99%